Characterizing the Role of Animal Exposures in Cryptosporidiosis and Shiga Toxin‐producing Escherichia coli Infections: South Dakota, 2012. (5th January 2016) - Daly, R. F.; Hill, N. T.
Summary: Cryptosporidium spp. and Shiga toxin‐producing Escherichia coli strains (STEC) are important causes of human illness. Incidence rates of these illnesses are high in South Dakota compared to the USA as a whole. Direct animal contact has been identified as a possible route of exposure for these illnesses. Ruminant animals may carry STEC subclinically, while young ruminants are common sources of zoonotic strains of Cryptosporidium . South Dakota patients with either STEC or cryptosporidiosis during 2012 were interviewed regarding seven categories of animal exposure: (i) petting zoo/fair attendance, (ii) animal event/rodeo attendance, (iii) feed/pet store visits, (iv) farm visits, (v) employment or residence at a farm, (vi) residence with pets and (vii) visiting other households with pets. Of the 50 STEC cases, 78.0% reported animal exposure prior to illness onset, with 23.3% having lived or worked on a farm. Farm visitors in particular had high degrees of animal contact and infrequently practiced personal protective measures. Of the 115 cryptosporidiosis cases, 87.8% reported animal exposures, with 45.6% having lived or worked on a farm and 29.0% having visited a farm prior to illness. Cases with farm exposures reported a high degree of direct animal contact and inconsistent use of personal protective measures. Cryptosporidiosis patients were significantly more likely than STEC patients to have lived or worked on a farm prior to their illness and were older on average. Patients with these illnesses had high rates of animal contact prior to illness. Animal contact on farms emerged as an important exposure route. Educational messages about personal protective measures should be directed at these individuals.